Acid Hydrolysis of Pretreated Sugarcane Bagasse, Macroalgae Sargassum sp. and Its Mixture in Bioethanol Production - Wunna, Kyaw; Auresenia, Joseph; Abella, Leonila; Gaspillo, Pag-asa; Nakasaki, Kiyohiko (Applied Science and Engineering Progress, 2023)
Sustainable biofuel feedstock could become a critical issue in the light of the recent fuel crisis. The use of mixed biomass could reinforce to overcome this issue. The present work examined the parallel use of agricultural residue sugarcane bagasse (SCB) and natural invasive marine seaweed Sargassum sp. (SSP) as a single feedstock and its mixture in two-step concentrated acid hydrolysis followed by yeast fermentation in order to produce reducing sugar with minimal formation of furfural, and bioethanol. In this work, alkali pretreated SCB and SSP were used as feedstock in acid hydrolysis. To investigate the influenced parameters of acid hydrolysis, biomass type (SCB, mixed biomass MB (SCB and SSP in 1:1 ratio by weight) and SSP), initial acid concentration (64–80 wt%), reaction time (30–90 min) and solid loading (10–20%w/w) were optimized by using Taguchi method. The optimized conditions were obtained with mixed biomass type, the initial acid concentration of 64 wt%, reaction time of 60 min and solid loading of 10%w/v. Under these conditions, 0.51 g/g of reducing sugar was achieved without furfural formation although ethanol yield was relatively low compared to that of Taguchi experimental runs. The result indicated that biomass type highly influenced the acid hydrolysis on sugar yield and furfural formation. This study provides the potential route for converting pretreated cellulosic biomass to value-added products, such as sugar and ethanol via the biorefinery process.